Floristic composition and management of vegetation cover in organic vineyard - Simić, Aleksandar (Acta herbologica, 2023)
In the organic cultivation of the Panonia grape variety in the Belgrade vine region, the vegetation cover in the vineyard is maintained with minimal intervention. It consists of spontaneous flora with occasional reseeding of grass and legume species. This study examined the composition of the vegetation cover after two years of irrigation at 50% and 100% of ETc (crop evapotranspiration) and compared it to a non-irrigated area. Irrigation was applied in 2021 and 2022, and floristic composition was recorded in spring 2023. It was found that the weed flora in the organically managed vineyards consists predominantly of hemicryptophytes and therophytes (mainly biennial and perennial species from the hemicryptophyte group). This indicates that the weed flora tends towards a weed-ruderal-meadow character in terms of floristic composition. In contrast to the flora life spectrum, the vegetation life spectrum provides a somewhat more realistic picture. Quantitatively (in terms of the number of individuals per unit area), biennial and annual species dominate, and the community is characterised as therophytic-hemicryptophytic.
Keywords: organically managed vineyard, irrigation, vegetation cover, biodiversity, Grocka wine subregion